The Effects of Academisation on Disadvantaged Students in English Secondary Schools - Towers, Scott (2018)
Increasing social mobility has been a policy priority of successive governments with the academies programme being seen as a solution by both governing parties. The purpose of this dissertation is to investigate the impact of the academies programme on improving social mobility. The four Chain Effects reports from The Sutton Trust (2014-2017) are analysed in order to do this as they are the largest data source available on the performance of academies in relation to disadvantaged students. Interviews with three headteachers are also used to investigate any differences in the strategies used by leaders to enhance social mobility that may be related to the freedoms and opportunities produced by successive acts of parliament. The findings show that academies have used GCSE ‘equivalents’ excessively to raise their performance figures whilst struggling to maintain these improvements under the new performance measures introduced in 2014. However, there are some examples of academy chains that do improve the life chances of disadvantaged students and these chains may be best placed to develop others through a self-improving system. This dissertation is limited by the small sample size of headteachers interviewed. However, these interviews do provide valuable insights into how macro-policy is enacted in context.